2009
DOI: 10.1111/j.1365-2982.2008.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

The multi‐herbal drug STW 5 (Iberogast®) has prosecretory action in the human intestine

Abstract: There is growing evidence that STW 5 (Iberogast), fixed combination of hydroethanolic herbal extracts), besides being effective in functional dyspepsia, also improves symptoms in irritable bowel syndrome (IBS). Clinical data indicate that modulation of mucosal secretion is a promising approach to treat intestinal disorders associated with IBS. We therefore explored the effect of STW 5 on secretion in the human intestine and the mechanisms by which it acts. The Ussing chamber technique was used to measure mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
2
31
0
2
Order By: Relevance
“…Our data is consistent with other studies utilizing glibenclamide at similar concentrations in isolated rat distal colon [31], human intestinal epithelial cells [39] and isolated murine ascending colon [29]. Recent evidence suggests the importance of an alternative Cl -channel to CFTR that is present in intestinal epithelia which is regulated by a PKA-independent, Epac-mediated pathway [40].…”
Section: Discussionsupporting
confidence: 82%
“…Our data is consistent with other studies utilizing glibenclamide at similar concentrations in isolated rat distal colon [31], human intestinal epithelial cells [39] and isolated murine ascending colon [29]. Recent evidence suggests the importance of an alternative Cl -channel to CFTR that is present in intestinal epithelia which is regulated by a PKA-independent, Epac-mediated pathway [40].…”
Section: Discussionsupporting
confidence: 82%
“…To test the effects of the H 2 S donor NaHS on ion secretion in intact submucosa/mucosa preparations of guinea-pig and human intestine we employed Ussing chamber techniques (Easy Mount chambers, Physiologic Instruments, San Diego, CA, USA) as previously described in detail 12,23 . The area of the recording chamber was 0.5 cm 2 .…”
Section: Ussing Chamber Experimentsmentioning
confidence: 99%
“…39 STW 5 may have other effects, including modulating intestinal afferent sensitivity as shown in male Wistar rats 40 and some of its components exert antispasmolytic, prosecretory, and anti-inflammatory effects in the small intestine and colon in animal models. 41,42 A randomized placebo-controlled trial using STW 5 in patients with functional dyspepsia for 8 weeks showed it to have a slightly better improvement in Gastrointestinal Symptom Score (GIS) compared with placebo with no difference in adverse effects. 43 Another randomized placebo double-blind study of patients with functional dyspepsia also documented improvement in the GIS in those randomized to STW 5, but no acceleration in gastric emptying in those with documented gastroparesis.…”
Section: Alternative Medicine For Gastroparesismentioning
confidence: 99%